The Influence of Brand Image and Customer Trust on Repurchase Interest and the Role of E-Word of Mouth To Customers of PT. Jasa Kopra Sejati in Pasuruan - Alfiadi; Survival; Mulyono (Optima Science, 2025)
This study aims to obtain empirical evidence of the effect of brand image, customer trust, e-word of mouth on customer repurchase intention of PT Jasa Kopra Sejati in Pasuruan. The primary data used in this study are data obtained directly from respondents which include data about customers of PT Jasa Kopra Sejati totaling 97 respondents. This study uses a quantitative approach research approach with hypothesis testing that is causal or causal. Data collection in this study was carried out using cross section time horizon data, where data was obtained at a certain time. The results of this study explain: 1) The effect of Brand Image on Repurchase Interest; 2) The effect of Customer Trust on Repurchase Interest; 3) The effect of E-Word of Mouth on Repurchase Interest; 4) The role of E-Word of Mouth in moderating the effect of Brand Image on Repurchase Interest; 5) The role of E-Word of Mouth in moderating the effect of Customer Trust on Repurchase Interest.